Analisis Peran Vegetasi Ruang Terbuka Hijau terhadap Kualitas Air Permukaan di Kawasan Permukiman Padat Kota Makassar - I Wayan Sudiyanto; Hasanuddin Molo; Rizki Amaliah; Sri Misykat Azis; Sri Magfirah HS (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2026)
Urban development and land conversion in residential areas of Makassar have increased pressure on surface water quality through domestic wastewater discharge, runoff, and reduced infiltration areas. The degradation of riparian vegetation and green open spaces (RTH) may reduce the ecological functions of urban waters, including filtering pollutants and maintaining environmental balance. Therefore, this study aimed to analyze the role of RTH vegetation in maintaining surface water quality in urban settlements using a quantitative descriptive approach. Surface water samples were collected from two rivers and one pond, while the analyzed parameters included pH, DO, BOD, COD, TSS, ammonia, fecal coliform, and total coliform based on Class II water quality standards and Pollution Index (PI) calculations. The results showed that BOD and COD exceeded the quality standards, while other parameters remained within acceptable limits. Pollution Index values ranged from 2.82 to 3.02, indicating lightly polluted conditions. Vegetation in the study area was dominated by Nypa fruticans, Sonneratia caseolaris, Rhizophora mucronata, Samanea saman, and Swietenia mahagoni, which contributed to reducing runoff and maintaining water stability. However, the vegetation had not effectively reduced organic pollution from domestic activities and land-use change. These findings indicate that green open spaces act as ecological buffers and support sustainable water quality management in Makassar by promoting vegetation conservation and improving domestic waste management.